2017
DOI: 10.1088/1361-6498/aa7f06
|View full text |Cite
|
Sign up to set email alerts
|

Dose estimation to eye lens of industrial gamma radiography workers using the Monte Carlo method

Abstract: The ICRP Statement on Tissue Reactions (2011), based on epidemiological evidence, recommended a reduction for the eye lens equivalent dose limit from 150 to 20 mSv per year. This paper presents mainly the dose estimations received by industrial gamma radiography workers, during planned or accidental exposure to the eye lens, Hp(10) and effective dose. A Brazilian Visual Monte Carlo Dose Calculation program was used and two relevant scenarios were considered. For the planned exposure situation, twelve radiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Thus, physical, biological and computational reconstructive dosimetry methods have been commonly used to review radiation doses estimated for radiological accidents. The Brazilian reconstructive dosimetry cases, for which the computer program 'Visual Monte Carlo Dose Calculation' were used, showed that it has been effective in quick estimation of radiation doses for organs and especially for cases of where radioactive sources have been handled in accidental exposures [8,9,19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, physical, biological and computational reconstructive dosimetry methods have been commonly used to review radiation doses estimated for radiological accidents. The Brazilian reconstructive dosimetry cases, for which the computer program 'Visual Monte Carlo Dose Calculation' were used, showed that it has been effective in quick estimation of radiation doses for organs and especially for cases of where radioactive sources have been handled in accidental exposures [8,9,19].…”
Section: Introductionmentioning
confidence: 99%